二氧化碳封存環境下對封固材料基本性質影響之研究 - 郭俊志; Kuo, Chun-Chih (2016)
在二氧化碳地質封存技術(CCS)部分，二氧化碳可以以超臨界流體狀態被注入深部地質構造與地底下的鹽水結合形成碳酸。造成注入井位材料退化或地質缺陷，其中在封固材料部份，二氧化碳可能的洩漏途徑包括套管與固井水泥(岩層與固井水泥)介面、套管與固井水泥裂縫或固井水泥(套管、岩層)退化等。 因此本研究設計一套超臨界二氧化碳反應器，提供二氧化碳封存對封固材料影響之相關研究，透過試驗室規模模擬台灣現地先導場址實際封存二氧化碳情況對其封固材料(固井水泥、頁岩)的影響，提出相關數據及分析結果，研究結果分述如下: (1) 本研究依據前人研究之二氧化碳試驗反應範圍及參考台灣先導場址井下環境之參數值，設計一套超臨界二氧化碳反應器。 (2) 觀察出API G級固井水泥在超臨界二氧化碳+水層環境反應完之損傷度較在超臨界二氧化碳層反應後之損傷度大。 (3) 利用超臨界二氧化碳反應器進行錦水頁岩模擬封存反應。結果觀察反應後有微小碳酸鈣沉澱礦物結晶產生。而岩樣試體滲透率及孔徑分佈，有隨反應時間增小的趨勢，有助於初期二氧化碳封存蓋層封固性。 (4) 利用超臨界二氧化碳反應器進行關刀山砂岩模擬封存反應。結果觀察到反應過後岩樣試體滲透率及孔徑分佈，有隨反應時間增大的趨勢，有助於初期超臨界二氧化碳於儲存層流通性。 (5) 自行設計複合樣本模擬試驗，探討複合樣本介面受二氧化碳封存之反應機制。 (6) 取得國外商用抗二氧化碳水泥並自行設計改質抗二氧化碳水泥，並完成水泥受二氧化碳侵蝕相關物理化學機制之探討。 In view of the technology for geological storage of carbon dioxide (CCS) carbon dioxide in its supercritical fluid state can be injected into the depth of the geological structure which combines with underground brine to form carbonic acid causing injected well material degradation or geological defects As for the sealing material routes that possibly lead to carbon dioxide leakage include: casing and oil well cement cap rock/oil well cement interface casing and oil well cement cracks or oil well cement casing and cap rock degradation etc Therefore a set of supercritical carbon dioxide reactor systems was designed in this study for research related to the impact of carbon dioxide storage on sealing materials The impact of the current situation of actual carbon dioxide storage at the existing pilot plant in Taiwan on oil well sealing cement and cap rocks was simulated on a laboratory scale in order to propose relevant data and analysis results Hence this study attempted to simulate on a laboratory scale the impact of the current situation of actual carbon dioxide storage at the existing pilot plant in Taiwan on oil well sealing cement and cap rocks to propose relevant data and analysis results (1) Based on the carbon dioxide test reaction ranges adopted by predecessors and in reference to the parameters for the well environment in Taiwan’ pilot plant a set of supercritical carbon dioxide reactors was designed (2) According to observations the degree of injury sustained by API G Grade oil well cement after the reaction with supercritical carbon dioxide + ground water environment was completed was greater than the degree of injury sustained after the supercritical carbon dioxide layer reaction was completed (3) Through the supercritical carbon dioxide reactor cap rock storage reaction simulation was carried out Based on the observation results a small amount of calcium carbonate mineral crystalline was produced As for rock sample permeability and pore size distribution the trend of “a decrease with reaction time” was seen which was conducive to the sealing of carbon dioxide storage rock cap during the early phase (4) The supercritical carbon dioxide reactor was used to simulate the storage reaction in the storage layer Observation results show that after the reaction the rock sample’s permeability and pore size distribution showed the trend of “an increase with reaction time” which was conductive to the circulation of the supercritical carbon dioxide in the storage layer during the early phase (5) The compound sample simulation test was self-designed to explore the compound sample interface’s reaction mechanism for the carbon dioxide in storage (6) Carbon dioxide cement for commercial use was acquired from abroad It was self-designed and modified into carbon dioxide-resistant cement In addition a discussion on the physical and chemical mechanism related to the cement under carbon dioxide erosion was completed